Sensitivity of Total Protein Creatinine Ratio in Urine for Diagnosis Diabetic Nephropathy - . Fatrinawati; . Windarwati; Osman Sianipar (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2017)
ABSTRACTDiabetic nephropathy is one of diabetic complication characterized by proteinuria and impaired renal function. Confirmation of diagnosis based either on urine value of albumin excretion rate (AER) 30-300 mg/24 hours or albumin creatinine ratio (ACR) 30-300 mg/g or total protein creatinine ratio (TPCR) 150-500 mg/g. It is reported that TPCR measurement is more acceptable since it is convenient, fast and does not require special preparation. The aim of this study is to investigate the accuracy of TPCR for diagnosis of diabetic nephropathy among type 2 diabetic patients.This was a diagnostic test study which involves 86 type 2 diabetic patients where urine TPCR value equal or more than 150mg/g was independently and blindly compared with AER as a refference standard to diagnose diabetic nephopathy. The inclusion criteria were type 2 diabetic patients that suspected suffer from diabetic nephropathy (long of illness is more than 4 years) and agree to participate in this study. Those whom were suffer from at least on of the following diseases urinary tract infection, congestive heart failure, liver dysfunction, pregnancy, multiple myeloma, microangiopathy hemolytic anemia (MAHA) and incomplete data were excluded from the study. The results of the study were analyzed using 2x2 table in order to calculate sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), likelihood ratio for positive test result/LR(+),likelihood ratio for negative test result/LR(-),and accuracy. The average of TPCR among diabetic nephropathy patient was 248.07 mg/g. It was significantly higher as compared to those non diabetic nephropathy patient (103.52 mg/g). It was found 75 true positive result, 9 true negative result, and 2 false positive result. The result showed that TPCR had a sensitivity, specificity, positive predictive value, and negative predictive value of 97.4%, 100%, 100%, and 81,8% respectively to diagnose diabetic nephropathy.Total Protein Creatinine Ratio (TPCR) with value equal or more than 150 mg/g in the morning sample urine can be used to diagnose diabetic nephropathy.Keywords: diabetic nephropathy, total protein creatinine ratio, sensitivity, albumin excretion rate, diagnostic test study